Phytofabrication of silver nanoparticles using Averrhoa bilimbi leaf extract for anticancer activity - Hublikar, Leena V; Ganachari, Sharanabasava V; Patil, Veerabhadragouda B (Nanoscale advances, 2023)
Averrhoa bilimbi leaf extract was successfully utilized as a reducing agent to synthesize silver nanoparticles (AgNPs) in the laboratory. The phytochemicals in the extract helped keep the silver nanoparticles stable and slowed them down. Different methods, such as UV-visible, FT-IR spectroscopies, XRD, and SEM analyses, were used to characterize the size, shape, and morphology of the nanoparticles, and the results showed that the synthesized nanoparticles were spherical and monodispersed. FTIR spectrum streaching vibrations shown stabillization of silver nanoparticles by green extract. On the other hand, these nanoparticles were labelled as Averrhoa bilimbi (AB) extract silver nanoparticles (AB-AgNPs). The biological synthesis process was proven to enhance the efficacy of the synthesized silver nanoparticles. The effectiveness of AB-AgNPs in fighting cancer could be enhanced specifically for lung cancer (A549 cell line) and breast cancer (MCF7 cell line) by optimizing the necessary conditions. The IC50 value for A549 cells was 49.52 g mL-1, while that for MCF7 cells was 78.40 g mL-1. The effect of AgNPs on both cell lines was assessed using an MTT assay, which showed a dose-dependent cytotoxicity effect. The biosynthesized AB-AgNPs hold great potential as anticancer agents. Their synthesis using Averrhoa bilimbi leaf extract as a reducing agent was proven to be successful, resulting in spherical and monodispersed nanoparticles that exhibit effective cytotoxicity against cancer cells.